The Effect Of Good Corporate Governance And Sustainability Report Disclosure On Banking Financial Performance - Rahmadita, Salsabilla; Marsono, Marsono (Tax Accounting Applied Journal, 2024)
This research aims to analyze the effect between the board of directors, audit committee, and disclosure of economic, social, and environmental aspects. The research population consists of banking companies listed on the IDX during the period 2017-2021. Using the purposive sampling technique for sample selection, a total of 55 research samples were selected for each year from 2017 to 2021. The hypotheses were tested using multiple linear regression analysis. The findings of this study indicate that the board of directors has a significant positive correlation, while the audit committee has a significant negative correlation with the ROA of banking companies. However, the disclosure of economic, social, and environmental aspects does not have a significant on the ROA of banking companies. Simultaneously, the board of directors, audit committee, and disclosure of economic, social, and environmental aspects significantly impact the ROA of banking companies.